Find The Ratio Of Areas

Geometry Level pending

In the figure above, A B C D ABCD is a square and C E = A F = A B 4 CE = AF = \dfrac{AB}4 . Find the ratio of the area of triangle E G H EGH : : the area of quadrilateral A F G H AFGH .

2 : 11 2:11 3 : 11 3:11 4 : 13 4:13 3 : 13 3:13

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Let the side length of square A B C D ABCD be 1 1 . Then A F = 1 4 AF = \dfrac 14 and the area of A E F \triangle AEF , [ A E F ] = 1 2 × 1 4 × 1 = 1 8 [AEF] = \dfrac 12 \times \dfrac 14 \times 1 = \dfrac 18 .

Since both E F EF and B D BD pass through the center of square A B C D ABCD , it is clear to see that G G is the center of square A B C D ABCD . Then the height of D G E \triangle DGE , G I = 1 2 GI = \dfrac 12 and its area [ D G E ] = 1 2 × G I × D E = 1 2 × 1 2 × 3 4 = 3 16 [DGE]=\dfrac 12 \times GI \times DE = \dfrac 12 \times \dfrac 12 \times \dfrac 34 = \dfrac 3{16} .

Let H J = a HJ=a be perpendicular to C D CD . Since D H J \triangle DHJ and D B C \triangle DBC are similar, H J D J = C D B C = 1 D J = H J = a \dfrac {HJ}{DJ} = \dfrac {CD}{BC} = 1 \implies DJ=HJ = a . Similarly, H E J \triangle HEJ and A E D \triangle AED are similar and E J = 3 4 a EJ= \dfrac 34 a . We have D J + E J = D E a + 3 4 a = 3 4 a = 3 7 DJ+EJ = DE \implies a + \dfrac 34 a = \dfrac 34 \implies a = \dfrac 37 . Then [ D H E ] = 1 2 × 3 4 × 3 7 = 9 56 [DHE]=\dfrac 12 \times \dfrac 34 \times \dfrac 37 = \dfrac 9{56} .

Now we have [ E G H ] [ A F G H ] = [ D G E ] [ D H E ] [ A E F ] [ E G H ] = 3 16 9 56 1 8 3 16 + 9 56 = 3 11 \dfrac {[EGH]}{[AFGH]} = \dfrac {[DGE]-[DHE]}{[AEF]-[EGH]} = \dfrac {\frac 3{16}-\frac 9{56}}{\frac 18 - \frac 3{16}+\frac 9{56}} = \dfrac 3{11}

Therefore [ E G H ] : [ A F G H ] = 3 : 11 [EGH]:[AFGH] = \boxed{3:11} .

Paul Nabonita
Apr 4, 2020

Let AB = a

(DGE) = (DE*Height)/2 = 3 a 2 3a^{2} /16

Triangle ABH ~ Triangle EDH

Therefore, AB/DE = Height JH/ Height IH = 4/3

So, IH = 3a/7

(EDH) = (DE*IH)/2 = 9 a 2 9a^{2} /56

(EGH) = (DGE) - (EHD) = 3 a 2 3a^{2} /112

(AFE) = (AF*AD)/2 = a 2 a^{2} /8

(AFGH) = (AFE) - (EGH) = 11 a 2 11a^{2} /112

Therefore, (EGH)/(AFGH) = 3/11

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...